Pembuatan Trainer Kelistrikan Sepeda Motor Untuk Program Studi Teknik dan Bisnis Sepeda Motor SMK Yapin Kertasemaya, Indramayu - Fitriyanto, Indra; Kurniawan, Yudhy; Maknunah, Jauharotul (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2023)
Project Based Learning is really needed in vocational schools, because education in vocational schools emphasizes the skills aspect rather than the knowledge aspect. So that this learning can be better understood by students, it is necessary to create a trainer or simulator to practice the theory that has been obtained. Based on a survey that has been conducted, the service partner, namely SMK Yapin Kertasemaya, has a Business and Motorcycle Engineering Study Program, but does not yet have a motorbike trainer. Therefore, this service will collaborate with partners, namely SMK Yapin Kertasemaya, to create motorbike trainers. Because the motorbike system is quite complex, the trainers made are limited to electrical trainers only. The trainer was made in the Instrumentation and Control Laboratory at the Indramayu State Polytechnic with the assistance of laboratory assistants and several students. So that the trainer created can function well, the trainer will also be tested and evaluated by expert lecturers from Mechanical Engineering. Based on the design that has been carried out, the results obtained are that all trainer components can function well and can be tested on vocational school students. After the trainer was tested on vocational school students, the team gave a questionnaire to the teachers and the results showed that the trainer made was very good and really helped the learning activities of vocational school students, but the quantity needed to be increased further in order to accommodate all students' practical activities.